SERVICE EXCELLENCE OF BARISTA SERVICES AT POTOCOFFEEMILKSHAKE TANJUNG BALAI KARIMUN RIAU ISLAND PROVINCE - Ikhsanul Rafi; Andi M Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The city of Tanjung Balai Karimun has a good tourism potential, with a strategic location and rich culture. Many types of tourism industry are developing in the city of Tanjung Balai Karimun, one of which is culinary tourism, most of them are coffee shops or cafes which are growing rapidly. This research aims to determine the implementation of a barista's duties in carrying out services at PotoCoffee Milkshake Tanjung Balai Karimun. This research is in correlation to service delivery with some aspects such as speed, accuracy, friendliness and skill. This research uses a qualitative method with a qualitative descriptive approach to describe and explain the situation that occurs by collecting data and information in the field. The key informants in this research are the Manager, Supervisors, Barista and customers at PotoCoffee Milkshake Tanjung Balai Karimun. In this research, the data collection techniques used were interviews, observation and documentation. The results of this research affirms that the implementation of services has been carried out based on Standard Operating Procedures related to speed, accuracy, friendliness, and barista skills itself. Keywords: Implementation, Service, Barista, Karimun Regency.